2007
DOI: 10.1111/j.1435-5957.2007.00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Supplying safe water in Bangladesh: A policy model based on multi‐objective mixed integer programming

Abstract: At present, about 80 million people in Bangladesh are at risk of losing their health and having a sharply reduced life expectancy as a result of exposure to excessive arsenic through drinking water from tube wells. In this article, we build a multi-objective mixed-integer optimisation model, which we can simulate. We identify efficient loci of the trade-off between the several competing objectives in order to provide safe water to the affected people. Three types of simulation cases are discussed. For each cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In recent years, several scholars have applied dynamic models and a simulation approach to conduct studies on integrated urban water resource management. These studies consider the connection of water resource, water pollution and economic development, and evaluate the economic and environmental impacts of integrated water management including wastewater treatment, water utilization and water reclamation (Mizunoya et al, 2006;Akmam & Higano, 2007;Xiang et al, 2014). However, most of these researches concentrate on the developed regions with a focus on water quality; there is a lack of early-warning studies for developing mining cities with consideration of both water allocation and water reclamation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several scholars have applied dynamic models and a simulation approach to conduct studies on integrated urban water resource management. These studies consider the connection of water resource, water pollution and economic development, and evaluate the economic and environmental impacts of integrated water management including wastewater treatment, water utilization and water reclamation (Mizunoya et al, 2006;Akmam & Higano, 2007;Xiang et al, 2014). However, most of these researches concentrate on the developed regions with a focus on water quality; there is a lack of early-warning studies for developing mining cities with consideration of both water allocation and water reclamation.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors contribute to low preparedness and adoption rates, such as the habits and attitudes of individuals (Hadi 2003), lack of public awareness (Jakariya et al 2003), existing poverty, distrust of government agencies and nongovernment organizations (NGOs) (Smith et al 2000), lack of education, and poor risk communication mechanisms (Hoque et al 2004). Akmam and Higano (2007) reported that in many cases different government and nongovernment organizations suggest that local communities adopt various technologies for getting safe water, free from arsenic and salinity contamination. But the results from tests conducted on different technologies are sometimes contradictory (Hoque et al 2004), and the local communities are confused as to how to select the most appropriate technology.…”
Section: Introductionmentioning
confidence: 99%